2023
DOI: 10.3389/fendo.2023.1131395
|View full text |Cite
|
Sign up to set email alerts
|

Age at diagnosis, diabetes duration and the risk of cardiovascular disease in patients with diabetes mellitus: a cross-sectional study

Abstract: BackgroundThe purpose of the study was to evaluate characteristics and risk of cardiovascular disease (CVD) according to age at diagnosis and disease duration among adults with diabetes mellitus (DM).MethodsThe association between age at diagnosis, diabetes duration and CVD were examined in 1,765 patients with DM. High risk of estimated ten-year atherosclerotic cardiovascular disease (ASCVD) was performed by the Prediction for ASCVD Risk in China (China-PAR) project. Data were compared with analysis of varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…53,54 The elevated risk of cardiovascular diseases in patients with T2D increases with age at diagnosis. 55,56 In our study, the patients especially in the "increasing" BMI group were younger than those in the "stable" BMI group and the hazard ratios for both microvascular and macrovascular complications become clearly significant after adjusting for age in model 2.…”
Section: Bmi Trajectories and Diabetes Complicationsmentioning
confidence: 50%
“…53,54 The elevated risk of cardiovascular diseases in patients with T2D increases with age at diagnosis. 55,56 In our study, the patients especially in the "increasing" BMI group were younger than those in the "stable" BMI group and the hazard ratios for both microvascular and macrovascular complications become clearly significant after adjusting for age in model 2.…”
Section: Bmi Trajectories and Diabetes Complicationsmentioning
confidence: 50%
“…De Jong et al [22], in a prospective cohort study of UK Biobank participants, described that a 5-year increase in the duration of diabetes was associated with a cardiovascular risk increase of around 20%. Yao et al [23] also reported that the duration of diabetes increases the 10-year cardiovascular risk. Thus, it seems important that the calculation of the 10-year cardiovascular risk in patients diagnosed with diabetes should consider the time of diagnosis of the disease.…”
Section: Discussionmentioning
confidence: 96%
“…The current data analysis was based on the prospective cohort study of 1765 Anhui adults with diabetes between March of 2018 and January of 2020. The cohort details have been described elsewhere [ 20 ]. Briefly, the participants joined a standard medical examination program provided by the CDCS study.…”
Section: Methodsmentioning
confidence: 99%